Alternative development policy for the Caribbean : the challenge of the development state approach - Karagiannis, Nikolaos (2002)
Introduces the strategic approach for the Caribbean region. Provides a brief discussion of the East Asian development experience. Identifies and highlights various economic development problems in the Caribbean. Focuses on a new development paradigm as well as on general implications and policy considerations for Caribbean countries.